2017
DOI: 10.1016/j.amsu.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Is endovascular treatment with multilayer flow modulator stent insertion a safe alternative to open surgery for high-risk patients with thoracoabdominal aortic aneurysm?

Abstract: A best evidence topic in cardiothoracic and vascular surgery was written according to a structured protocol. The question addressed was whether endovascular treatment with multilayer flow modulator stents (MFMS) can be considered a safe alternative to open surgery for high-risk patients with thoracoabdominal aortic aneurysm (TAAA). Altogether 27 papers were identified using the reported search, of which 11 represented the best evidence to answer the clinical question. The authors, journal, date and country of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…concluded that the implantation of MFMs is safe with few complications, although no randomized studies were available. 9 Most of the studies published to date included a few patients, usually less than 30, with a relatively short follow-up period of no more than 12 months. 5 , 6 , 7 , 8 , 10 , 11 , 12 , 13 , 14 , 15 A larger study with 103 patients was published by Sultan et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…concluded that the implantation of MFMs is safe with few complications, although no randomized studies were available. 9 Most of the studies published to date included a few patients, usually less than 30, with a relatively short follow-up period of no more than 12 months. 5 , 6 , 7 , 8 , 10 , 11 , 12 , 13 , 14 , 15 A larger study with 103 patients was published by Sultan et al .…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were rupture of aortic aneurysm, stenosis of branch arteries (arteries of head and neck, visceral and iliac arteries), occlusion of the aortoiliac segment, prior endovascular or surgical treatment of the same aneurysm, mycotic aneurysm, myeloproliferative blood disorders, known coagulopathies, and expected survival less than six months. 9 For each patient, a consultation was held with Cardiatis (Isnes, Belgium) before the procedure to obtain their consent for MFM implantation.…”
Section: Methodsmentioning
confidence: 99%